Study of the Forces Affecting the KVLCC2 Tanker and the Propeller MP687 Using the Verification and Validation Procedure and CFD - حاتم وهاد; رامي حوا; نوار عباس (Latakia University Journal -Engineering Sciences Series, 2024)
This research presents a detailed explanation of the Verification and Validation procedure followed in CFD (Computational Fluid Dynamic) and EFD (Experimental Fluid Dynamic) studies. This procedure ensures the method’s correctness and the settings used in these studies. V&V was applied to the case of the forces affecting the KVLCC2 tanker and its propeller using the CFD. The URANS (Unsteady RANS Averaged Navier Stocks Equations) and the k-Ꞷ SST turbulence model was used to solve the Navier Stokes equations. KVLCC2 tanker model (Korean Very Large Crude Carrier 2nd Generation) was selected to conduct this study due to the availability of many EFD results for this ship model, which may help us be sure about the quality of the numerical results we will get. Initially, the ship model was studied alone without any appendages. The open water test was also conducted on the ship’s propeller. Then, the results were subject to Verification and Validation procedure to demonstrate the accuracy of the equations and turbulence model used.